2017
DOI: 10.1515/prilozi-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Perioperative Prophylaxis with Cefuroxime or Ceftriaxone in the Surgical Site Infections Prevention after Cranial and Spinal Neurosurgical Procedures

Abstract: introductionSurgical site infections pose a significant problem in the treatment of neurosurgical procedures, regardless of the application of perioperative prophylaxis with systemic antibiotics. The infection rate in these procedures ranges from less than 1% to above 15%. Different antibiotics and administration regimes have been used in the perioperative prophylaxis so far, and there are numerous comparative studies regarding their efficiency, however, it is generally indicated that the choice thereof should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…Dimovska-Gavrilovska et al in their study found that the administration of parenteral antibiotics before surgery reduces the incidence of postoperative infections after neurosurgical procedures, especially in cases with increased risk factors for SSIs. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Dimovska-Gavrilovska et al in their study found that the administration of parenteral antibiotics before surgery reduces the incidence of postoperative infections after neurosurgical procedures, especially in cases with increased risk factors for SSIs. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Se analizaron un total de 40 pacientes asignados aleatoriamente a los dos EPP. Los autores demostraron que ambos EPP mostraron un comportamiento estadístico similar 13 . En otro estudio, realizado en un centro hospitalario de cirugía endoscópica de base de cráneo en Italia, se analizaron todos los casos desde 1998 a 2005.…”
Section: Discussionunclassified
“…In cases such as septic arthritis, osteomyelitis, and spondylodiscitis, antibiotics can be used in long-term, high, and repeated doses (7,22,25,38). In addition to their side effect profile, antibiotics used in this way may also have adverse effects that cause toxicity, particularly during surgery, to avoid such negativities (9,10,17,22,25,27,31). RQ = 0.9, respectively.…”
Section: █ Discussionmentioning
confidence: 99%